Time on feedlot and sexual effects on animal performance and characteristics of lamb’s meat (Acta Scientiarum. Animal Sciences, 2017)
For this research 48 male lambs were divided in randomized blocks in a factorial design, having as factors sexual condition (castrated or uncastrated) and time on feed (36 or 78 days). High grain diet was monitored daily to measure the performance of the animal nutrition. The characteristics of the carcass and meat were taken for the fatty acids profile and sensorial analysis. The effect of the factors as sexual condition and time on feed, and the interaction between them, were evaluated by analysis of variance using the GLM procedure of SAS software and the treatment averages were compared by Student's T test. The uncastrated animals presented greater weight gain and dry matter intake, better feed efficiency, and larger loin area. More time on feed resulted in higher weight at slaughter. Parameters such as pH, color, meat tenderness and sensorial attributes were not affected by treatments. For the fatty acid profile there was effects and interactions between sexual condition and time on feed. It is concluded that castration should not be used when the animal is young and slaughtered and feed intensively, but neutering can be interesting to improve the fatty acid profile of the meat.